ESTIMATION OF CHEBULAGIC AND CHEBULINIC ACID IN TERMINALIA CHEBULA - T. N. RANJINI; M. A. SURYANARAYANA; K. BHANUPRAKASH; UMESHA (The Bioscan, 2015)
Terminalia chebula is an important medicinal tree, used in the treatment of many human ailments and it is one of the important constituent in Triphala ayurvedic drug along with Emblica officinalis and Terminalia bellerica. In the present investigation two important phytochemicals viz., chebulagic and chebulinic acid from dried fruits of twelve Terminalia chebula accessions located at Indian Institute of Horticultural Research were estimated using RP-HPLC method. Estimation of phytoconstituents was achieved by using C18 coloumn and acetonitrile - 0.05% of orthophosphoric acid in water with 0.0136% of anhydrous potassium dihydrogen orthophosphate (KH2PO4) as mobile phase at a flow rate of 1.5mL/min. Amongst twelve accessions, highest percentage of chebulagic and chebulinic acids were recorded in IIHRTc6 (21.10%) and IIHRTc7 (9.59%) accessions, respectively. These phytoconstituents content variation among Terminalia chebula accessions can be used as a maker in identification of best accessions for crop improvement programme.